Genetic Characterization of the Apple Germplasm Collection in Central Italy: The Value of Local Varieties - Marconi, Gianpiero; Ferradini, Nicoletta; Russi, Luigi; Concezzi, Luciano; Veronesi, Fabio; Albertini, Emidio (Frontiers in Plant Science, 2018)
In the last fifty years, intensive farming systems have been boosted by modern agricultural techniques and newly bred cultivars. The massive use of few and related cultivars has dramatically reduced the apple genetic diversity of local varieties, confined to marginal areas. In Central Italy a limited spread of intensive fruit orchards has made it possible to preserve much of the local genetic diversity, but at the same time the coexistence of both modern and ancient varieties has generated some confusion. The characterization and clarification of possible synonyms, homonyms and/or labeling errors in old local genetic resources is an issue in the conservation and management of living collections. 175 accessions provided by 10 apple collections, mainly local varieties, some of unknown origin, and well-known modern and ancient varieties, were studied by using 19 SSRs, analyzed by STRUCTURE, Ward’s clustering and parentage analysis. We were able to identify 25 duplicates, 9 synonyms and 9 homonyms. As many as 37 unknown accession were assigned to well known local or commercial varieties. Polyploids made up 20 %. Some markers were found to be significantly correlated with morphological traits and the loci associated with the fruit over colour were related to QTLs for resistance to biotic stresses, aroma compounds, stiffness and acidity. In conclusion the gene pool of Central Italy seems to be rather consistent and highly differentiated compared with other European studies (FST=0.147). The importance of safeguarding this diversity and the impact on the management of the germplasm living collection is discussed.